Vitamin D supplementation improves simvastatin‐mediated decline in exercise performance: A randomized double‐blind placebo‐controlled study1: 补充维生素D治疗可以改善辛伐他汀介导的运动功能下降:一项随机双盲安慰剂对照研究. (28th June 2017) - Singla, Mandeep; Rastogi, Ashu; Aggarwal, Ashutosh N.; Bhat, Owais M.; Badal, Darshan; Bhansali, Anil
Abstract: Background: The aim of the present study was to determine the effect of vitamin D supplementation on simvastatin‐mediated changes in cardiorespiratory fitness and skeletal muscle mitochondrial content after exercise in adults with type 2 diabetes mellitus (T2DM). Methods: Vitamin D‐deficient T2DM patients aged 25–50 years performed moderate intensity aerobic exercise for 12 weeks and were randomized to receive simvastatin 40 mg daily, simvastatin 40 mg daily plus vitamin D 60 000 units once weekly, or vitamin D 60 000 units once weekly. The primary outcomes were cardiorespiratory fitness (peak oxygen consumption) and skeletal muscle mitochondrial content (citrate synthase activity in the vastus lateralis) following simvastatin and/or vitamin D replacement therapy. Results: Twenty‐eight patients completed the study. Cardiorespiratory fitness decreased by 8.4% ( P   <  0.05) following 12 weeks of simvastatin therapy. Vitamin D supplementation blunted the decline in cardiorespiratory fitness to 0.6% ( P   <  0.05 for between‐group difference in change from baseline). Similarly, skeletal muscle mitochondrial content decreased by 3.6% with simvastatin, but improved by 12.1% on supplementation with vitamin D, although the between‐group difference was not significant. Vitamin D alone increased cardiorespiratory fitness and mitochondrial content by 7.1% ( P   <  0.05) and 16.7%, respectively. Conclusions: Simvastatin tends to cause deterioration in exercise‐associated cardiorespiratory fitness and skeletal muscle mitochondrial content in adults with T2DM, which is blunted by vitamin D supplementation. Abstract : Highlights Vitamin D supplementation attenuates the simvastatin‐mediated decline in exercise‐associated cardiorespiratory fitness and skeletal muscle mitochondrial content in patients with type 2 diabetes. It is useful to replete patients with vitamin D before starting statin therapy.